2016
DOI: 10.1002/mrm.26525
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring acute metabolic changes in the liver and kidneys induced by fructose and glucose using hyperpolarized [2‐13C]dihydroxyacetone

Abstract: Purpose To investigate acute changes in glucose metabolism in liver and kidneys in vivo after a bolus injection of either fructose or glucose, using hyperpolarized [2‐13C]dihydroxyacetone. Methods Spatially registered, dynamic, multi-slice MRS were acquired for the metabolic products of [2-13C]dihydroxyacetone in liver and kidneys. Metabolism was probed in 13 fasted rats at three time points: 0, 70 and 140 minutes. At 60 minutes, rats were injected intravenously with fructose (n=5) or glucose (n=4) at 0.8 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…Absorption of the DHA into cells and its conversion into metabolically active DHAP, likely dictate the degree to which DHA can perturb metabolic pathways and induce oxidative stress. This is consistent with recent work injecting hyperpolarized [2‐ 13 C] DHA into mice, which showed rapid distribution of DHA to the liver and kidneys and metabolism of DHA to DHAP by liver and kidney cells, but showed different conversion rates of DHAP to glyceraldehyde 3‐phosphate depending on tissue type …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Absorption of the DHA into cells and its conversion into metabolically active DHAP, likely dictate the degree to which DHA can perturb metabolic pathways and induce oxidative stress. This is consistent with recent work injecting hyperpolarized [2‐ 13 C] DHA into mice, which showed rapid distribution of DHA to the liver and kidneys and metabolism of DHA to DHAP by liver and kidney cells, but showed different conversion rates of DHAP to glyceraldehyde 3‐phosphate depending on tissue type …”
Section: Discussionsupporting
confidence: 92%
“…Melanocytes and melanoma cells have the potential to be exposed to DHA throughout the epidermis and dermis, and the bioenergetics of the melanoma make it likely that exogenous DHA will be metabolized . While the transport mechanism by which DHA enters into cells still needs to be determined, it is clear that exogenous DHA can enter cells and alter metabolism in a tissue and cell specific manner . Thus, it is important to evaluate potential exposure effects, noting that there have been no studies examining the effect of DHA exposure on mucous membranes, which may occur during spray tanning …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first HP injection and scan applied 1 H decoupling, whereas the second injection and scan (approximately 90 min later, within the same scanning session) did not. A previous study applying similar methods showed that the extent of conversion of HP [2‐ 13 C]DHA to HP [2‐ 13 C]G3P in liver and kidney returns to a similar level within 80 min after the first injection . For in vivo experiments, effectiveness of decoupling was verified just before the HP experiment based on signal from a vial phantom containing 1‐mL [2‐ 13 C]glycerol (Cambridge Isotopes, Tewksbury, Massachusetts) placed adjacent to the rat.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, certain HP probes of interest with long T 1 relaxation times and minimal 1 H couplings are enzymatically transformed in vivo to important metabolic products with major 1 H couplings. This can occur with dehydrogenase activity at the labeled carbon site, exemplified by the reduction via lactate dehydrogenase of HP [2-13 C]pyruvate to [2][3][4][5][6][7][8][9][10][11][12][13] C]lactate (9), which is observed as a well-resolved 13 C signal doublet at 3 T (J ¼ 146 Hz). Elimination of such large couplings, however, introduces high decoupling power requirements, which in turn require exceptionally good isolation between multinuclear RF channels, which is not typical for clinical MRI systems.…”
Section: Introductionmentioning
confidence: 99%